Religion and Religiosity seen in Hawthorneâs The Scarlet Letter - , DEA MAHARANI SADEWI, Dr. Juliasih, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper investigates Nathaniel Hawthorneâs The Scarlet Letter. The research attempts to discover Hawthorneâs perception toward Puritans in which they are hypocrites. They are people who have religion but their attitude and behavior are far from religiosity. The objectives of this paper are to see the differences between religion and religiosity and to find out the deviation of the Puritans as religious people. The analysis covers the hypocrite of Puritan, Hawthorneâs perception toward Puritans, self-contemplation that experienced by Hester. Hester is a character which commits sin, but she has high religiosity. Through Hester, Hawthorne wants to criticize Puritans society, because their attitude does not reflect as people with religion. This research uses the expressive approach by Abrams. The theory is related to the work and author. The data of this research is collected by library research analyzed by descriptive method. The result tells that a person who has religion will be meaningless if there is no religiosity in it. Religiosity is important for every person, in order to create balance between relationship to God and humanity. That is why, they do not become hypocrites.